Phenotypic Characterization of High Carotenoid Tomato Mutants Generated by the Target-AID Base-Editing Technology - Hunziker, Johan; Nishida, Keiji; Kondo, Akihiko; Ariizumi, Tohru; Ezura, Hiroshi (Frontiers in Plant Science, 2022)
Our previous study demonstrated that Target-AID which is the modified CRISPR/Cas9 system enabling base-editing is an efficient tool for targeting multiple genes. Three genes, SlDDB1, SlDET1 and SlCYC-B, responsible for carotenoid accumulation were targeted, and allelic variations were previously obtained by Target-AID. In this research, we characterized the effect of new alleles on plant growth and fruit development, as well as carotenoid accumulation, individually in segregating backcross populations or combined in null self-segregant lines. Only lines carrying homozygous substitutions in the three targeted genes and the segregating backcross population of individual mutations were characterized, resulting in the isolation of two allelic versions for SlDDB1, one associated with SlDET1 and the last one with SlCYC-B. All edited lines showed variations in carotenoid accumulation, with an additive effect for each single mutation. These results suggest that Target-AID base-editing technology is an effective tool for creating new allelic variations in target genes to improve carotenoid accumulation in tomato.